2021
DOI: 10.3390/ijms22105166
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Histologic Adaptation of Horned Gall Induced by the Aphid Schlechtendalia chinensis (Pemphigidae)

Abstract: Chinese galls are the result of hyperplasia in host plants induced by aphids. The metabolism and gene expression of these galls are modified to accommodate the aphids. Here, we highlight the molecular and histologic features of horned galls according to transcriptome and anatomical structures. In primary pathways, genes were found to be unevenly shifted and selectively expressed in the galls and leaves near the galls (LNG). Pathways for amino acid synthesis and degradation were also unevenly shifted, favoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…HCT is a crucial enzyme in the initial stages of lignin biosynthesis, primarily involved in the production of lignin and the extension of fiber length (Besseau et al., 2007; Lu, Kai, et al., 2021; Weng & Chapple, 2010). Histological studies have revealed that the formation and development of CG are accompanied by lignification (Hirano et al., 2020; Lu, Chen, et al., 2021). Here, we constructed a biosynthetic pathway diagram of lignin and analyzed the expression levels of multiple genes in the pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HCT is a crucial enzyme in the initial stages of lignin biosynthesis, primarily involved in the production of lignin and the extension of fiber length (Besseau et al., 2007; Lu, Kai, et al., 2021; Weng & Chapple, 2010). Histological studies have revealed that the formation and development of CG are accompanied by lignification (Hirano et al., 2020; Lu, Chen, et al., 2021). Here, we constructed a biosynthetic pathway diagram of lignin and analyzed the expression levels of multiple genes in the pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, most LAC and HCT gene family members showed identical expression patterns and were highly expressed in SG and RG (Figure 3c; Table S31). Histological investigations have demonstrated that the lignification of secondary cell walls leads to the hardening of the CG's outer epidermal cell layer (Hirano et al., 2020; Lu, Chen, et al., 2021). These lignin biosynthesis genes may contribute to the construction of CG structures.…”
Section: Discussionmentioning
confidence: 99%
“…A few genes involved in the Calvin cycle were found to be significantly upregulated in galled tissues compared with ungalled tissues. Considering that there were no stomas in the inner galled tissues, this promotion of the Calvin cycle may be attributable to the CO 2 produced during gall mite respiration inside the gall, as shown in the galls of D. vitifoliae and Schlechtendalia chinensis [ 15 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phytohormones related to cell growth and cell division, such as auxins (AUXs) and cytokinins (CKs), generally increase in galls [ 11 , 12 ]. Tissues inside galls are usually rich in sugar, proteins, amino acids and other nutrients [ 13 , 14 , 15 ], and tissues outside galls are abundant in phenols, flavonoids and other secondary metabolites [ 16 , 17 , 18 , 19 ]. Meanwhile, the activity of oxidative enzymes such as superoxide dismutase (SOD), catalase (CAT), peroxidase (POD) and polyphenol oxidase (PPO) [ 20 , 21 ], and defense-related phytohormones such as salicylic acid (SA) and jasmonic acid (JA) [ 22 ], are also enhanced during gall development.…”
Section: Introductionmentioning
confidence: 99%
“…The sequences of the target genes were selected based on transcriptomes generated from previous studies (transcriptomes were submitted to the National Centre for Biotechnology Information Sequence Read Archive database, and can be found at the following sites: https://www.ncbi.nlm.nih.gov/bioproject/PRJNA631065 and https://www.ncbi.nlm.nih.gov/bioproject/PRJNA662477 ) [ 43 , 44 ]. Specific primers were designed using Primer-primer 6.0, and the relative quantification method was used, with the first stage leaf samples as the control and tubulin as the reference gene.…”
Section: Methodsmentioning
confidence: 99%